(untitled) (International Journal of Engineering and Computer Science, 2015)
Carbon Nanotubes (CNTs) have generated great interest for their potential as reinforcement in high performance cementitious composites. Zeolites reduce the chloride permeability and increases workability in the cement mortar. The proper dispersion of carbon nanotubes and zeolites in the cement mortar plays an important role in this study. The experimentation will be performed in 1:3 cement mortar for different water cement ratio of 0.55 to 0.7, 0.1% of multiwalled carbon nanotubes, 0.5% of Polycarboxylate Superplasticizer and 1% of zeolite. Flow on different water cement ratio of cement mortars were tested. The specimens of size 50mm x 50mm x 50mm cube and 100mm diameter, 200mm height cylinders are used. Then the specimen is to be tested on7th day,28th day 90th days. The compressive strength, split tensile strength are being determined.